2019
DOI: 10.14476/jomp.2019.44.3.92
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of the Masticatory Function in Patients with Temporomandibular Disorders: A Cross-Sectional Cohort Study

Abstract: Purpose: To investigate the masticatory function of patients with different temporomandibular disorders (TMD) phenotypes, and to explore the risk factors for the masticatory function of TMD patients among multiple biopsychosocial variables using patient-reported outcomes (PROs). Methods:Clinical features and TMD diagnoses of 250 cases were investigated by reviewing medical records. Psychosocial factors were evaluated using four questionnaires representing pain severity and pain interference (Brief Pain Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…None of the included biomedical factors affected the jaw functional limitation. Our previous study included a pain‐free TMD group with ID (n = 14) and compared it with the painful TMD groups, which was consistent with Fetai et al 39 The results of our previous study (Part I) showed that pain‐free TMD group with ID presents less jaw functional limitation than painful TMD (χ 2 = 9.534, p = 0.023) 12 …”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…None of the included biomedical factors affected the jaw functional limitation. Our previous study included a pain‐free TMD group with ID (n = 14) and compared it with the painful TMD groups, which was consistent with Fetai et al 39 The results of our previous study (Part I) showed that pain‐free TMD group with ID presents less jaw functional limitation than painful TMD (χ 2 = 9.534, p = 0.023) 12 …”
Section: Discussionsupporting
confidence: 84%
“…Fetai et al 39 The results of our previous study (Part I) showed that pain-free TMD group with ID presents less jaw functional limitation than painful TMD (χ 2 = 9.534, p = 0.023). 12 The mean global scores of the JFLS-20 of patients with ID (presented in the previous study) were 0.8 (SD 0.9), 1.4 (SD =1.4), 0.2 (SD = 0.6) and 0.9 (SD = 0.7) for mastication, mobility, communication and global score, respectively. In the comparison of JFLS-20 scores of individuals who were lifetime negative for TMD in the OPPERA study, 38 jaw functional limitation of the patients with ID seems to be higher than those of controls showing the mean scores of 0.28 (SD 0.02), 0.18 (SD 0.02), 0.14 (0.02) and 0.16 (0.02) for mastication, mobility, communication and the global score, respectively.…”
Section: Biomedical Risk Factors For Jaw Functional Limitationmentioning
confidence: 78%
See 3 more Smart Citations